Quilombolas frente aos efeitos sociais do agronegócio: estratégias de luta e resistência no território de Saco das Almas em Brejo/Buriti-MA - Caldas, Jaine de Jesus Alves (2022)
Conflicts between holders of capital and people who directly depend on territory for its material and symbolic reproduction highlight the correlation of forces existing in the capitalist system, which, in the unbridled search for the accumulation of profit, operates based on a colonialist logic. The art. 68 of the Provisions Act Transitional Constitutions ensure the rights of the remnants of quilombos over their territories, with the State being responsible for issuing the titles. However, the dichotomy between the legal and the real is accentuated in the Brazilian structure, promoting uncertainty and threats to these communities. In this context, Saco das Almas is located, a quilombola territory, located in East Maranhão, in the municipalities of Brejo and Buriti, incorporated by the dynamics of Matopiba, agricultural frontier presented as a development plan by the Brazilian government since 2015. The new frontier region contains a significant number of traditional populations, which begin to suffer constant attacks from agribusiness. From this perspective, the This research aims to investigate the organizational processes of resistance of the quilombolas of Saco das Almas to face the social effects of agribusiness in the region of Brejo/Buriti-MA. During this journey, two bases are adopted methodological, which privilege both the analysis of the totality of processes social, in order to an understanding oriented beyond the apparent, as a methodology rooted in the opposition of the logic of modernity/coloniality, as prioritizes local and border stories; therefore, the materialist method applies historical-dialectical and the decolonial proposal. Saco das Almas is identified as a territory quilombola not titled by the responsible body, implicating the residents of the communities at imminent risk as a result of the expansion of soybean fields. Before of the predatory nature of the capitalist mode of production, the quilombolas place themselves in a position of struggle and resistance to defend the right to territory, the maintenance of life and a liberating project anchored in another type of society, Good Living